The Impact of Auditor Competence and Internal Control Systems on Audit Quality at Cirebon Regional-Owned Enterprises and the Cirebon City Inspectorate - Faoziyyah Isfahani; Ida Rosnidah (CV. AFDIFAL MAJU BERKAH, 2026)
This study aims to analyze the effect of Auditor Competence and Internal Control System on Audit Quality at the Regional-Owned Enterprises (BUMD) of Cirebon and the Inspectorate of Cirebon City. The population comprised 45 internal auditors and employees directly involved in the audit process, and a census sampling technique was employed so that all members of the population were included as the study sample. This research adopted an associative quantitative approach, grounded in Agency Theory. Data were collected through questionnaires using a 5-point Likert scale and analyzed using multiple linear regression with IBM SPSS. The results of the normality test produced an Asymp. Sig. value of 0.062 (>0.05), confirming that the data were normally distributed. The multicollinearity test yielded Tolerance = 0.427 and VIF = 2.339, indicating no multicollinearity among the independent variables. The regression equation was formulated as Y = 11.862 + 0.098X1 + 0.508X2. Auditor competence (X1) had a positive and significant effect on audit quality (t = 3.725, sig. < 0.001, β = 0.098). The internal control system (X2) also had a positive and highly significant effect and constituted the most dominant factor (t = 27.921, sig. < 0.001, β = 0.508). Simultaneously, both variables had a positive and significant effect on audit quality (F = 1112.098, sig. < 0.001), with an Adjusted R² of 0.981, indicating that 98.1% of the variation in audit quality is explained by these two variables, while the remaining 1.9% is attributed to other factors. The conclusion of this study confirms that the Cirebon Regional-Owned Enterprise (BUMD) and the Cirebon City Inspectorate need to prioritize strengthening the internal control system and the ongoing development of auditor competencies to improve audit quality, as these two factors complement each other in supporting the realization of professional, independent, and high-quality internal audits.